The Donut Diaries of Dermot Milligan - McGowan, Anthony; Illustration by Tazzyman, David (UK A Corgi Book, 2011)
Not only does Dermot have to write down how many donuts he eats, but also - and this is the really rubbish part - he has to talk about HIS FEELINGS! But things are about to get even worse - he's being separated from his friends and sent to St Michael's, a posh school where he just knows he's going to stick out like a sore thumb
Include Illustration
Keywords: Diaries -- Diary fiction